An Integrated Methodology for the Emergency Logistics Centers Location Selection Problem and its Application for the Turkey Case - Tuzkaya, Umut Rifat; Yilmazer, Kadriye Busra; Tuzkaya, Gulfem (WALTER DE GRUYTER GMBH, 2015)
Urgent response is vitally important after unpredictable disasters and it is highly dependent to the location of the emergency centers. Considering this importance degree, in this study, a location selection methodology for emergency logistics centers (ELCs) is proposed. There are various influencing factors or criteria to choose the most convenient locations for ELCs. However, we focused on some of the most important and prior criteria to obtain a more feasible approach and less calculation intensity. The main point is ranking and weighting the convenient locations or cities for constructing an ELC in a region or country. The alternative locations are chosen through the mostly natural disaster-prone cities. Decision criteria are determined according to the expert opinions. Decision Making Trial and Evaluation Laboratory (DEMATEL) and Analytic Network Process (ANP) methods are integrated to determine the convenient locations considering the relations between criteria and alternative locations. Afterwards, a real life application of the proposed methodology is realized for the Turkey case. Finally, results are examined and analyzed in terms of their sensitivity on the criteria weight changes.
Keywords: ANP; DEMATEL; emergency logistics; locational analysis; multi-criteria decision making; ROBUST OPTIMIZATION; MODEL; Public Administration